Basic Atomic Interactions of Accelerated Heavy Ions in Matter Atomic Interactions of Heavy Ions - Tolstikhina, Inga (Springer Series on Atomic, Optical, and Plasma Physics,, 2018)
This book provides an overview of the recent experimental and theoretical results on interactions of heavy ions with gaseous, solid and plasma targets from the perspective of atomic physics. The topics discussed comprise stopping power, multiple-electron loss and capture processes, equilibrium and non-equilibrium charge-state fractions in penetration of fast ion beams through matter including relativistic domain. It also addresses mean charge-states and equilibrium target thickness in ion-beam penetrations, isotope effects in low-energy electron capture, lifetimes of heavy ion beams, semi-empirical formulae for effective cross sections. The book is intended for researchers and graduate students working in atomic, plasma and accelerator physics.